2021
DOI: 10.1021/acs.nanolett.1c01295
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Nonradiative Point Defects Buried in Quantum Wells Using Cathodoluminescence

Abstract: Crystallographic point defects (PDs) can dramatically decrease the efficiency of optoelectronic semiconductor devices, many of which are based on quantum well (QW) heterostructures. However, spatially resolving individual nonradiative PDs buried in such QWs has so far not been demonstrated. Here, using high-resolution cathodoluminescence (CL) and a specific sample design, we spatially resolve, image, and analyze nonradiative PDs in InGaN/GaN QWs at the nanoscale. We identify two different types of PDs by their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 67 publications
3
22
0
Order By: Relevance
“…30 Finally, the last option is to enhance the recombination rate. This could be achieved by reducing the QW thickness, 31 increasing the driving current 32 or by using semi-polar or non-polar structures. Additional simulations, showing the impact of these parameters on the IQE, are presented in SI Section III.…”
mentioning
confidence: 99%
“…30 Finally, the last option is to enhance the recombination rate. This could be achieved by reducing the QW thickness, 31 increasing the driving current 32 or by using semi-polar or non-polar structures. Additional simulations, showing the impact of these parameters on the IQE, are presented in SI Section III.…”
mentioning
confidence: 99%
“…Additionally, we assume the carrier lifetime to decrease with increasing temperature due to thermal activation of defects, although different studies showed an opposite trend. [ 23,25 ] The dependencies of the effective carrier lifetime on temperature in these studies are small, changing with a factor of about 2. In another study by Nippert et al, the temperature change of the ABC parameter was investigated.…”
Section: Resultsmentioning
confidence: 79%
“…To examine the optical quality of the MQWs, the IQE is often estimated by first assuming the IQE is 100% at low temperature and referencing the PL efficiency, defined as η PL = I PL P laser , at room temperature to the PL efficiency measured at the same laser power density and low temperature (<20 K). However, this assumption is not always valid because there are some nonradiative processes that are active below 20 K. [ 33–35 ] In order to minimize the error from this assumption, the PL efficiency was measured by varying the laser power density and temperature. The IQE was then estimated by normalizing to the maximum PL efficiency measured at 14 K, where the radiative rate dominates over the nonradiative rate, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%